Virulence factors and antibiotic resistance of Helicobacter pylori isolated from raw milk and unpasteurized dairy products in Iran - Mousavi,Soolmaz (2014)
Background Despite the high importance of Helicobacter pylori, the origin and transmission of this bacterium has not been clearly determined. According to controversial theories and results of previous studies, animal source foods – especially milk – play an important role in the transmission of H. pylori to humans. The aim of the present study was to determine the distribution of vacA, cagA,iceA and oipA virulence factors inH. pylori strains isolated from milk and dairy products and study their antimicrobial resistance properties.Methods A total of 520 raw milk and 400 traditional dairy product samples were cultured and tested. Those that were H. pylori-positive were analyzed for the presence of vacA,cagA, iceA and oipAvirulence factors. Antimicrobial susceptibility testing was performed by the disk diffusion method.Results One hundred and three out of 520 milk samples (19.8%) and 77 out of 400 dairy products samples (19.2%) were contaminated with H. pylori. The most frequently contaminated samples were ovine milk (35%) and traditional cheese (30%). Total prevalence ofvacA, cagA, iceA andoipA factors were 75%, 76.6%, 41.6% and 25%, respectively. H. pylori strains of milk and dairy products harbored high levels of resistance to ampicillin (84.4%), tetracycline (76.6%), erythromycin (70.5%) and metronidazole (70%).Conclusions High presence of antibiotic-resistant strains of H. pylorisuggest that milk and dairy samples may be the sources of bacteria that can cause severe infection. Our findings should raise awareness about antibiotic resistance in H. pylori strains in Iran.